Introduction: Revitalizing Collegiality: Restoring Faculty Authority in Universities - Ulla Eriksson-Zetterquist; Kerstin Sahlin (Emerald Publishing Limited, 2023)
Collegiality is often discussed and analyzed as a challenged form of governance, a form of working that used to function well in universities prior to the emergence of contemporary and modern forms of governance. This seems to suggest that collegiality used to dominate, while other forms of governance are now taking over. The papers in volume 86 of this special issue support the notion of challenged collegiality, but also show that for the most part, nostalgic notions of “the good old days” are neither true nor helpful if we are to revitalize academic collegiality. After examining whether a golden age of collegiality ever existed, we discuss why collegiality matters. Exploring what are often described as limitations or “dark sides” of collegiality, we address four such “dark sides” related to slow decision-making, conflicts, parochialism, and diversity. This is followed by a discussion of how these limitations may be handled and what measures must be taken to maintain and develop collegiality. With a brief summary of the remaining papers under two headings, “Maintaining collegiality” and “Revitalizing collegiality,” we preview the rest of this volume.
10.1108/S0733-558X20230000087001; 10.1108/S0733-558X20230000087001; Revitalizing Collegiality: Restoring Faculty Authority in Universities; EBP099697181